Learning Outcomes with Linked Assessments – an Essential Part of our Regular Teaching Practice - Ann C. Smith (American Society for Microbiology, 2010)
Setting up learning outcomes with linked assessments is a best practice in science education. In biology teaching, faculty are beginning to establish learning outcomes and assessments in the style of concept inventories. At a recent meeting of biology faculty who have designed concept inventories, the characteristics and uses of concept inventories were defined. Concept inventories used as pre- and post-measures of student learning provide a window into students’ understanding of key concepts of a discipline and serve as a tool to motivate faculty toward evidence-based teaching habits. A movement for the development of a microbiology concept inventory is suggested.